POTENTIAL CHEMOPREVENTIVE AGENT: STUDY OF APOPTOSIS IN THE EXTRACTS OF SPONGE-ASSOCIATED FUNGI FROM YOGYAKARTA AGAINST CERVICAL CANCER HeLa CELL LINE - Eka Ramadhani; Fajar Priyambada; Abrory Agus Cahya Pramana; Aditya Nur Subchan; Gian Aditya Pertiwi; Raden Aditya Aryandi Setiawibawa; Hendy Eka Putra; Nur Rofika Ayu Shinta Amalia; Nastiti Wijayanti (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Cervical cancer is one of the leading-cancers affecting women. Cancer drugs that do not originate from natural ingredient, chemotherapy drugs, have side and resistant effects. Thus study about the natural products treating cancer cells is needed. Secondary metabolites isolated from sponge-associated fungi are expected to have a potency to fight cancer cells. In addition, the production of anticancer compounds from microorganisms has several advantages, including rapid growth and can be manipulated to increase productivity. The isolation and testing cytotoxicity against 3 fungal isolates from Yogyakarta have been done on the previous research. All three isolates have a potential candidate as anticancer drug. Aims: The purpose of this advanced study was studying bioactive compounds induced apoptosis pathway of sponge-associated fungi against cervical cancer HeLa cells. Methods: This study has been carried out for approximately 5 months. The method conducted in this research including the sponge cultivation (covers growth and isolation of secondary metabolites), the mycelium extraction of fungi, the cytotoxicity assay against HeLa cells using MTT Assay and Apoptosis Staining was to see the induction of apoptosis pathway. Results: Based on the research showed that ethyl acetate extract from mycelium is 0.22 grams. The cytotoxicity assay from mycelium extract showed IC50 value of 164 μg/mL against HeLa cell line. Conclusion: The findings is carrying to a possibility to develop the extracts of sponge-associated fungi as candidate of anti-cancer compound. By apoptosis staining, showed the cells coloured green are still alive, and cells undergoing apoptosis have nucleus that appears orange to red. We assuming that the apoptosis was caused by the possibility of peptide compounds that induce apoptosis through the mitochondrial pathway, by increasing the activity of the protein expression of apoptosis, which are Bcl-2 and Bcl-xl.